Report of therapeutic failure of Fenbendazole, Levamisole and Ivermectin in the control of gastrointestinal nematodes in dairy cattle (Bos taurus) in Cajamarca, Peru - Rojas-Moncada, Juan (2023)
The present study evaluated the efficacy of fenbendazole, levamisole and ivermectin in the control of nematodes in dairy cattle farms in three provinces of the Cajamarca region, Peru. Thirty female cattle older than six months were selected in each farm (E-I, E-II, E-III), distributed in three homogeneous groups (n=10) according to the natural infection loads of gastrointestinal nematodes. Using an active principle for each treatment, fenbendazole (oral) and levamisole (subcutaneous) were administered at a dose of 7.5 mg/kg and ivermectin at 0.2 mg/kg (subcutaneous). It was determined that in E-I there was therapeutic failure to fenbendazole (70.05 ± 6.57% efficacy) and levamisole (52.08 ± 7.07%) and in E-II to levamisole (65.06 ± 7.25%) and ivermectin (73.96 ± 6.62%). In E-III, levamisole and fenbendazole were effective (99.13 ± 0.98% and 100%, respectively). The larvae obtained after dosing were Trichostrongylus spp and Ostertagia spp in E-I, Haemonchus spp and Ostertagia spp in E-II, and Trichostrongylus spp and Ostertagia spp in E-III.